Research of Electronic Information Systems - Balaišis, P.; Eidukas, D.; Besakirskas, A.; Tervydis, P.; Gočelkienė, L. (Elektronika ir Elektrotechnika, 2005)
The main objective of our paper is to present the subjects of quality, efficiency and reliability of electronic devices (ED), electronic systems (ES) and electronic information systems (EIS), which are analyzed by paper coauthors in their works. Structure of theory of EIS quality will be presented in the paper. Conceptions of quality, value and efficiency, which describe the EIS, will be given. Efficiency is the best illustration of EIS features; therefore, detailed structure of the general efficiency theory will be presented. Review of parameters that affect efficiency will be made. Efficiency often is identified with probability of tasks accomplishment, and as the main element used in EIS structure is electronic device (ED), subject of ED reliability will be widely presented in the paper. For illustration, trends of research of efficiency (reliability) dynamics and persistence will be shown. Ill. 12, bibl.5 (in English; summaries in Lithuanian, English and Russian).